Theoretical model of the plastic zone at the I-mode crack tip in dentin. (May 2017) - Borodin, E.N.; Gutkin, M. Yu; Mikaelyan, K.N.; Panfilov, P.
Abstract: Possible mechanisms of inelastic deformation at the I-mode crack tip in dentin are theoretically studied. We consider the relative shear of collagen fibers in their nodes without breaking intermolecular bonds, the detachment of collagen fibers from each other in the nodes, and tearing of the individual fibers. For each of these mechanisms, we estimate the size of the plastic zone near the crack tip and show that the detachment of collagen fibers is the easiest mechanism of inelastic deformation. Our estimates are in agreement with electron microscopy observations. Graphical abstract: